Attention deficit hyperactivity disorder (ADHD) in children and adolescents. Issue 3 (May 2015) - Said, Zead; Huzair, Hifzi; Helal, Muhammad Nabeel; Mushtaq, Imran
<x xml:space="preserve">Abstract</x> Estimates of the prevalence of attention deficit hyperactivity (ADHD) vary widely which has led to some controversy over the diagnosis. Nevertherless, it is recognised in DSM‐5 and as hyperkinetic disorder in ICD‐10. Here the authors compare diagnostic criteria of ADHD in DSM‐5 and ICD‐10 and review its management.